Push recovery control of quadruped robot using particle swarm optimization based structure specified mixed sensitivity H2/H∞ control. Issue 3 (11th March 2020) - Sutyasadi, Petrus; Parnichkun, Manukid
Abstract : Purpose: The purpose of this paper is to introduce a quadruped robot strategy to avoid tipping down because of side impact disturbance and a control algorithm that guarantees the strategy can be controlled stably even in the presence of disturbances or model uncertainties. Design/methodology/approach: A quadruped robot was developed. Trot gait is applied so the quadruped can be modelled as a compass biped model. The algorithm to find a correct stepping position after an impact was developed. A particle swarm optimization-based structure-specified mixed sensitivity ( H 2 / H ∞ ) robust is applied to reach the stepping position. Findings: By measuring the angle and speed of the side tipping after an impact disturbance, a point location for the robot to step or the foothold recovery point (FRP) was successfully generated. The proposed particle swarm optimization-based structure-specified mixed sensitivity H 2 / H ∞ robust control also successfully brought the legs to the desired point. Practical implications: A traditional H ∞ controller synthesis usually results in a very high order of controller. This makes implementation on an embedded controller very difficult. The proposed controller is just a second-order controller but it can handle the uncertainties and disturbances that arise and guarantee that FRP can be reached. Originality/value: The first contribution is the proposed low-order robust H 2 / H ∞ controller so it is easy to be programmed on a small embedded system. The second is FRP, a stepping point for a quadruped robot after receiving side impact disturbance so the robot will not fall.